The Role of Trade Unions In Industrial Relations: Examining the Various Roles of Trade Unions in Industrial Relations (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A trade union is an organization based on membership of employees invarious trades, occupations and professions, whose major focus is therepresentation of its members at the workplace and in the wider society. Theprimary purpose of a trade union is collective bargaining. The main objectiveof this paper is to study the different role of trade union.